2015
DOI: 10.1007/s11157-015-9382-6
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation and control of anaerobic digestion processes: a review and some research challenges

Abstract: 31To enhance energy production from methane or resource recovery from digestate, anaerobic digestion processes 32 require advanced instrumentation and control tools. Over the years, research on these topics has evolved and 33 followed the main fields of application of anaerobic digestion processes: from municipal sewage sludge to liquid 34-mainly industrial -then municipal organic fraction of solid waste and agricultural residues. Time constants of 35 the processes have also changed with respect to the treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 258 publications
0
89
0
2
Order By: Relevance
“…Historically, AD has mainly been associated with the treatment of sewage sludge from aerobic wastewater treatment and animal manure (Esposito et al 2012). Over the years, the main fields of AD application shifted from municipal sewage sludge to liquid (mainly industrial) wastewater, then to the municipal organic fraction of solid waste and agricultural residues (Jimenez et al 2015). While the first industrial scale digesters date back to the first half of the twentieth century, interest in AD of solid biowaste has rapidly increased since the energy crises of the 1970s (Cecchi and Cavinato 2015).…”
Section: Anaerobic Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, AD has mainly been associated with the treatment of sewage sludge from aerobic wastewater treatment and animal manure (Esposito et al 2012). Over the years, the main fields of AD application shifted from municipal sewage sludge to liquid (mainly industrial) wastewater, then to the municipal organic fraction of solid waste and agricultural residues (Jimenez et al 2015). While the first industrial scale digesters date back to the first half of the twentieth century, interest in AD of solid biowaste has rapidly increased since the energy crises of the 1970s (Cecchi and Cavinato 2015).…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…More on AD process inhibition due to ammonia, sulfide, light metal ions, heavy metals and other compounds is discussed in Chen et al (2008), Zhao et al (2010) and Yenigün and Demirel (2013). A review on the issue of instrumentation and process control can be found in Jimenez et al (2015), on mathematical models for both simulation and control purposes in Lauwers et al (2013), and on recent advances in the utilization of inorganic and biological additives to improve digester performance in Romero-Güiza et al (2016).…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…This is a crucial observation for operational issues. Indeed, in many AD plants, COD is measured instead of the methane yield because it is faster and easier to obtain [5]. However, this implies that COD and methane yield should be correlated.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the profitability of the process, a wide variety of substrates ranging from agricultural organic wastes to wastewater sludge need to be added to the feedstock mix for codigestion [4]. In this context, involving frequent changes in the recipe, the characterization of the substrate is crucial for monitoring the plant [5].…”
Section: Monitoring Approaches For Anaerobic Digestionmentioning
confidence: 99%
“…A shift in operation to a flexible regime as described will result in different requirements for instrumentation and monitoring. In addition to this, there is a lack of online measurements which makes monitoring and online control more challenging . Whilst there are online gas measurement systems available for the AD process, these also face some limitations, e.g., catalytic sensors can become damaged when exposed to hydrogen sulfide due to the oxidation of the gas resulting in a mineral acid which can lead to corrosion .…”
Section: Introductionmentioning
confidence: 99%